(untitled) (Kinesiology, 2019)
Taekwondo is striking Olympic combat sport where scoring actions are powerful and short-duration techniques, especially kicks. However, there are no many taekwondo-specific physical tests. Recently the frequency speed of kick test (FSKT10s) and its intermittent version (5 x 10s/10s intervals, FSKTmult) has been used to assess physical fitness of taekwondo and athletes, but no classificatory normative table was found for this test. Thus, the aim of present study was to present two normative classificatory tables for the FSKT10s and FSKTmult, one for males and another for females. One hundred fifteen male taekwondo athletes (median (interquartile range) age: 20 (17;27) years; height: 175 (170;182) cm; body mass: 67 (60;78) kg; experience time: 6 (3;10) years) and seventy female taekwondo athletes (median (interquartile range) age: 19 (17;24) years; height: 162 (157;169) cm; body mass: 57 (50;64) kg; experience time: 5 (3;9) years) volunteered to participate in the present study. The skills ranged between 4rd gub and 2rd dan. All the participants were evaluated during their competitive period and were familiarized with this test. Five scales were used (“Excellent” (≥95th percentile); “Good” (>75th percentile up to 94th percentile); “Regular” (>25th percentile up to 74th percentile); “Poor” (>6th percentile up to 24th percentile); and “Very poor” (≤5th percentile) after analysis of data distribution to classify FSKT10s and FSKTmult variables. Among male the tests were classified as follow: males - FSKT10s: ‘Excellent’: ≥24; ‘Good’: 22-23; ‘Regular’: 18-21; ‘Poor’: 17; ‘Very poor’: ≤16 kicks and FSKTtotal: ‘Excellent’: ≥108; ‘Good’: 97-107; ‘Regular’: 85-96; ‘Poor’: 80-84; ‘Very poor’: ≤79 kicks; females - FSKT10s: ‘Excellent’: ≥22; ‘Good’: 21; ‘Regular’: 17-20; ‘Poor’: 16; ‘Very poor’: ≤15 kicks and FSKTtotal: ‘Excellent’: ≥97; ‘Good’: 92-96; ‘Regular’: 82-91; ‘Poor’: 73-81; ‘Very poor’: ≤72 kicks. These classificatory tables can help coaches and strength and conditioning professionals to classify performance and monitor the physical fitness of taekwondo athletes in different training processes and during the competitive season.